The Visual Lexica of (National) Belonging and Nonbelonging in the Accounts of Young Kurds in Finland - Mari Toivanen (Nordic Journal of Migration Research, 2014)
This study argues in favour of including an analytical focus on in/visibilities in order to gain insights into the racialization processes as experienced by individuals who have become subjected to derogatory categorizations. This paper examines how individuals’ experiences of everyday racism relate to their struggles to belong. In this paper, I discuss how the theme of in/visibility emerges in the accounts of young Kurds, who have migrated to Finland at a young age and grown up in the country. What kind of visual lexica of belonging do they employ when narrating their experiences of everyday racism? And relatedly, how do they speak of boundaries of (national) belonging and nonbelonging? The results show that “Finnishness” denotes “racial” belonging to the nation. Young Kurds contrast “white Finnishness” with racializing categorizations that indicate non-belonging to the Finnish nation. They have been labelled with such categorizations in social situations in the public space or at work by people they have encountered. However, there is space for young Kurds to contest such racializing categorizations and to negotiate their belonging to Finland by mastering the Finnish language and, in some cases, having Finnish citizenship.